2020
DOI: 10.1088/1674-4527/20/9/143
|View full text |Cite
|
Sign up to set email alerts
|

A cold and diffuse giant molecular filament in the region of l = 41°, b = −1°

Abstract: Data of 12CO/13CO/C18O J = 1 → 0 emission toward the Galactic plane region of l = 35° to 45° and b = –5° to +5° are available with the Milky Way Imaging Scroll Painting (MWISP) project. Using the data, we found a giant molecular filament (GMF) around l ≈ 38° ∼ 42°, b ≈ –3.5° ∼ 0°, V LSR ≈ 27 ∼ 40 km s−1, named the GMF MWISP G041–01. At a distance of 1.7 kpc, the GMF is about 160 pc long. With a median excitation temperature about 7.5 K and a median column density about 1021 cm−2, this GMF is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Additionally, bundles of smaller scale 'fibers' have been found within those filaments (Hacar et al 2013(Hacar et al , 2016Henshaw et al 2016). Extremely long (even longer than 100 pc) and velocity coherent large-scale filaments (LSFs) have been observed in the Milky Way as part of spiral arms or inter-arm regions (Jackson et al 2010;Goodman et al 2014;Ragan et al 2014;Zucker et al 2015;Abreu-Vicente et al 2016;Li et al 2016;Du et al 2017;Zucker et al 2018;Lin et al 2020;Schisano et al 2020). As the physics of filaments appears tightly connected to star formation (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, bundles of smaller scale 'fibers' have been found within those filaments (Hacar et al 2013(Hacar et al , 2016Henshaw et al 2016). Extremely long (even longer than 100 pc) and velocity coherent large-scale filaments (LSFs) have been observed in the Milky Way as part of spiral arms or inter-arm regions (Jackson et al 2010;Goodman et al 2014;Ragan et al 2014;Zucker et al 2015;Abreu-Vicente et al 2016;Li et al 2016;Du et al 2017;Zucker et al 2018;Lin et al 2020;Schisano et al 2020). As the physics of filaments appears tightly connected to star formation (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…There is a possibility that the clouds are mere foreground or background sources of W50. As an example, Lin et al (2020) identified a giant molecular filament in the Milky Way Imaging Scroll Painting (MWISP) in front of the SS 433/W50 system in the velocity range from 27 to the molecular clouds that we identified and this giant molecular filament. Lin et al (2020) suggested that GMF MWISP G041-01 comprises four components, three being filamentary structures.…”
Section: Association With the Ss 433/w50 Systemmentioning
confidence: 86%
“…As an example, Lin et al (2020) identified a giant molecular filament in the Milky Way Imaging Scroll Painting (MWISP) in front of the SS 433/W50 system in the velocity range from 27 to the molecular clouds that we identified and this giant molecular filament. Lin et al (2020) suggested that GMF MWISP G041-01 comprises four components, three being filamentary structures. Two such giant filaments possibly collided in the region around (α J2000 , δ J2000 ) = (19 h 10 m 01.3525 s , +7 d 15 m 03.330 s ) and (19 h 10 m 29.6389 s , +6 d 10 m 32.713 s ), while they might be just overlapping along the line of sight.…”
Section: Association With the Ss 433/w50 Systemmentioning
confidence: 86%
“…As one of the fundamental components of the interstellar medium, molecular clouds mainly consist of molecular gas with a mixture of atoms, ions, dust, and other materials (Heyer & Dame 2015;Heiles et al 2019). The molecular clouds in the galaxy exhibits the structure over a wide range of scales, from 20 pc or more for giant molecular clouds down to 0.05 pc for dense molecular clumps (Williams et al 2012;Kauffmann et al 2013;Lin et al 2020). Modern astronomy proved that the formation of stars is inside the molecular clumps (Krumholz & McKee 2005;Zinnecker & Yorke 2007;Krumholz et al 2009).…”
Section: Introductionmentioning
confidence: 99%